The nutrient supplying capabilities of Uzinura, an endosymbiont of armoured scale insects. (1st January 2013) - Sabree, Zakee L.; Huang, Charlie Y.; Okusu, Akiko; Moran, Nancy A.; Normark, Benjamin B.
Summary An emerging common physiological feature of plant sap‐feeding insects is the presence of bacterial endosymbionts capable of providing essential nutrients to their host. These microbial partners are inviable outside of specialized host tissues, and therefore a cultivation‐independent approach, namely high‐throughput next‐generation genome sequencing, can be used to characterize their gene content and metabolic potential. To this end, we sequenced the first complete genome of the obligate endosymbiont, Candidatus 'Uzinura diaspidicola', of armoured scale insects. At 263 431 bp, Uzinura has an extremely reduced genome that is composed largely of genes encoding enzymes involved in translation and amino acid biosynthesis. The tiny size of the Uzinura genome parallels that observed in some other insect endosymbionts. Despite this extreme genome reduction, the absence of a known obligate partner bacterial symbiont suggests that Uzinura alone can supply sufficient nutrients to its host.